Sistema stand alone de contagem de células vermelhas de animais domésticos e silvestres - Kovalhuk, Gabriel (2012)
A RISC-based platform is proposed for supporting the counting of red blood cells of wild animals. This platform is aimed for semi-automatic counting of the cells from different species of animals where size and volume of cells can greatly differ. The results show that this system can automatically count most of the cells correctly with an average error of only 1.88% of false negatives and 1.82% of false positives. It’s possible for the user to manually correct the results where a work at most 3.70%. It´s also possible to storage the images for future use.